Self-determination mini-theories in second language learning: A systematic review of three decades of research - Al-Hoorie, Ali H.; Oga-Baldwin, W.L. Quint; Hiver, Phil; Vitta, Joseph P. (Language teaching research : LTR, 2025)
Self-determination theory is one of the most established motivational theories both within second language learning and beyond. This theory has generated several mini-theories, namely: organismic integration theory, cognitive evaluation theory, basic psychological needs theory, goal contents theory, causality orientations theory, and relationships motivation theory. After providing an up-to-date account of these mini-theories, we present the results of a systematic review of empirical second language research into self-determination theory over a 30-year period (k = 111). Our analysis of studies in this report pool showed that some mini-theories were well-represented while others were underrepresented or absent from the literature. We also examined this report pool to note trends in research design, operationalization, measurement, and application of self-determination theory constructs. Based on our results, we highlight directions for future research in relation to theory and practice.